Ultrasonik ve klasik yıkama yöntemlerinin dokuma kumaş termal özelliklerine etkilerinin incelenmesi - (:unkn) unknown (My University, 2012)
Bu çalışmada, iki farklı (ultrasonik ve klasik) yıkama yöntemi ile yıkanmış %100 pamuk, %100 polyester (PES) ve %50/50 pamuk/PES karışım dokuma kumaşların kuru ve nemli haldeki termal konfor özellikleri incelenmiştir. Yıkama sonrası termal konfor özelliklerinin nasıl değiştiğinin bilinmesi üretilecek kumaşın kullanım alanının belirlenmesinde faydalı olacaktır. Alambeta ve Permetest cihazları kullanılarak kumaşların termal özelliklerine, yıkama yöntemlerinin, kuru ve nemli hallerin ve lif türünün etkisi karşılaştırmalı olarak analiz edilmiştir. Elde edilen test sonuçları termal konfor özelliklerinin, yıkama metodu, kuru-nemli halde olma ve lif cinsine göre değiştiğini göstermektedir.

ABSTRACT: In this study, 100% cotton, 100% polyester and %50/50 cotton/PES woven fabrics were washed ultrasonically and traditionally. Determination of the thermal comfort properties of raw fabrics is important, however; the changes of the thermal comfort properties of the washed fabrics have also to be known for the better garment production. Thermal comfort properties of the unwashed and the washed fabrics' were tested in both dry and wet states. The investigation of the comfort properties were performed by using Alambeta and Permetest instruments. The effect of washing methods, dry and wet states, and of fibre types on thermal comfort properties were highlighted and compared. According to the test results the washing methods, dry-wet states and the fibre types have impact on the thermal comfort properties.
An investigation of the effects of ultrasonic and traditional washing methods on thermal comfort properties of woven fabrics